Bacteremia and infection of a hip prosthesis caused by Bacillus alvei. - Reboli, A C (1989)
Of the 34 Bacillus species described, 10 have been reported to cause infection in humans and 6 are insect pathogens. We report a case of an infected prosthetic hip caused by Bacillus alvei, only the third documented case of human infection with this organism.